Preface - Mesman, Judi (Student Undergraduate Research E-journal!, 2018)
Leiden University College (LUC) is very pleased to host the 2018 Student Research Conference (SRC). The SRC’s goals to celebrate and stimulate undergraduate research fits perfectly with LUC’s mission to provide a high-quality research-led teaching environment for talented bachelor students who have what it takes to make valuable contributions to academic inquiry. The list of nominated projects for this year’s conference clearly shows the breadth and depth of what undergraduate students can do when higher education institutes take them seriously and providing a stimulating learning environment.